Simple and Energy-Saving Modifications of Coal Fly Ash to Remove Simultaneously Six Toxic Metal Cations from Mine Effluents - Pizarro-Konczak, J (Elsevier Ltd, 2018)
Modifications of original coal fly ash at low and elevated temperatures with NaOH can all generate improvement in surface area, pore volume and cation exchange capacity. However, modifications at room temperature of fly ash and with a 7-day freezing/thaw cycle proved to be much more energy-effective and of enhanced applicability, compared to high temperature treatments. The contact time of fly ash in the NaOH liquor remarkably influenced the outcome of fly ash modification at room temperature. Surface area increased by 64- to 70-fold for room temperature and freezing/thaw forms, respectively, in comparison to original. Both treatments also greatly enhanced porosity and cation exchange capacities. Solution pH of systems was constantly monitored and adjusted to avoid any possible formation of metallic hydroxides. Adsorption kinetics and isotherms of Cu2+, Pb2+, Ni2+, Cr3+, Co2+ and Cd2+ were studied in synthetic combined solution and tailing pond water media. Both modified forms demonstrated their effectiveness in removing metal ions from both media. Adsorption kinetics fitted well with pseudo-second order model; adsorption isotherms fitted acceptably with both Langmuir and Freundlich models. Thermodynamic studies of Ni2+ and Cu2+ with the freezing/thaw form in the synthetic solution revealed that the adsorption process was favorable, although endothermic with a decrease in entropy. Column studies were also done to complement the batch mode approach, and showed a strong influence of flow rate and pH. The studies showed that low temperature NaOH treatment of fly ash is not only energy saving and economic, but also facilitates large-scale industrial applications. © 2018 Elsevier Ltd. All rights reserved.